Efektivitas Penggunaan PowerPoint Interaktif dalam Mendorong Kolaborasi dan Komunikasi Siswa - Abdullah, Radhinal; Nasution, Muhammad Irwan Padli (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research examines the effectiveness of using interactive PowerPoint as a tool to encourage collaboration and communication among students in an educational context. Interactive PowerPoints are used to facilitate group discussions, direct questions, and share visual materials that support active and participatory learning. Research methods include observation of learning sessions using interactive PowerPoint as well as data collection through surveys to evaluate student perceptions of the use of this tool. The results showed that the use of interactive PowerPoint significantly increased student participation in discussion and collaboration in groups. Students report a more enjoyable and immersive learning experience because these tools allow them to actively engage in the learning process. In addition, interactive PowerPoint helps students develop their communication skills, both in conveying ideas orally and in written form. These findings indicate that interactive PowerPoint is not only a tool for conveying information, but also an effective means for promoting student engagement and development. Collaboration and communication skills are crucial in 21st century education. The implication of this research is the importance of integrating interactive technology in teaching practices to support active learning and increase student engagement in the classroom.